(NkRISTALLIZACIQ I TERMOOBRABOTKA TONKIH PLENOK (B/s - (NtO^ICKIJ(B, (N|DUARD iWANOWI^s; (NsEWERDENKO(B, (Nw(B.(Np(B.s ((NmINSK (B:s (NnAUKA I TEHNIKA(B,s, 1976)
(NbIBL(B. 619 (NNAZW(B.s
(Nan bELORUSSKOJ ssr(B. (NfIZ(B.-(NTEH(B. (NIN(B-(NTs
Keywords: (NfIZI^ESKOE STROENIE MATERIIs